The impact of building information modeling on reducing greenhouse gases through design validation - Lee, Chijoo (Journal of Civil Engineering and Management, 2025)
This study proposes a method to reduce rework due to design errors by applying building information modeling (BIM) to reduce greenhouse gas (GHG) emissions during the construction stage. The study focuses on reducing waste in construction materials, transportation, and recycling, with the analysis grounded on expert opinions using fuzzy theory and life cycle inventory data. Applying the proposed method to the case building reduced emissions by 113,211 kg CO2eq, which is 64 times the GHGs emissions from driving a car or van for 10 or fewer passengers over 20,000 km. To offset 113,211 kg CO2eq, about 12,441–13,977 pine trees would be required. Reducing wasted concrete contributes to approximately 79.9% of the total GHGs emissions decrease. Among the buildings that started construction in South Korea between July 2022 and February 2023, 68.3% are reinforced concrete structures based on gross floor area. Applying BIM to these structures could yield even greater benefits than those reported in this study. This study also introduces a method based on fuzzy analytic hierarchy process (AHP) for decision makers to prioritize design changes. This method provides quantitative data to enrich qualitative discussions among construction, BIM, and estimation managers regarding design changes.